Economic Value of Malaysian Agricultural Multifunctionality - Choo, Kevin Wai Kit (2016)
Agriculture not only offers commercial outputs but also non-food benefits such like food security, environmental protection, landscape and cultural preservation and rural employment, known as agricultural multifunctionality. It provides externalities that should be crucial considerations for policy makers. As such, an economic valuation of agricultural multifunctionality would be timely for better decision-making with regards to agricultural and trade policies of Malaysia, especially since Malaysia’s growth has been driven by industrialization at the expense of the agricultural sector. The principal objective of this study is to estimate the economic value of agricultural multifunctionality using the contingent valuation method, which elicits the willingness-to-pay (WTP) of the public for it. It is expected that Malaysians in general would be happy to pay a little extra for agricultural products in order to enjoy the many positive externalities. It also seeks to find the sociodemographic variables among the general public that could influence this WTP. A pilot study is conducted to ascertain the level of interest in such externalities, followed by an in-person survey to estimate the willingness-to-pay for said externalities, using a payment card approach. An analysis was performed on the collected data. The result of the survey showed that a proportion of the public was willing to pay 6.02% of their spending on agricultural products to support agricultural sustainability initiatives. This study also estimated that the annual economic value of this spending could potentially be RM1.622 billion. Finally, this study makes several recommendations for the consideration of the government in terms of policies and further research.